The effect of tourism agglomeration on foreign real estate investment: evidence from selected OECD countries - Fereidouni, Hassan Gholipour; Masron, Tajul Ariffin (International Journal of Strategic Property Management, 2011)
The purpose of this study is to investigate the effect of tourism agglomeration on foreign real estate investment (FREI). Using a panel of 19 OECD countries over a period of 10 years (1999-2008) and controlling for some relevant factors, econometric analysis indicates that tourism agglomeration is a significant determinant of FREI. The result has some implications for policymakers in order to recover their real estate sectors which were hit in recent financial crisis.First Publish Online: 5 Oct 2011